2014
DOI: 10.1002/jnr.23530
|View full text |Cite
|
Sign up to set email alerts
|

The paired neuroglial and interglial membranes in the crayfish stretch receptor and their local disorganization

Abstract: The paired neuronal and glial membranes, or interglial membranes, which are separated by the narrow layer of the extracellular medium, are involved in intercellular communications. In the crayfish stretch receptor, the paired neuroglial membranes contain thin protein bridges (septate junctions) that maintain the intermembrane gap. In some places the paired membranes are locally disorganized. In the altered regions, they comprise the diffuse material in which a few 10-15 nm vesicles are embedded. The developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The spikes propagate to the ventral nerve cord ganglion [16][17][18] . The ultrastructure of this neuron was studied in detail in many works [19][20][21] . It proved itself a convenient model object for studying the response of neurons and glial cells to various damaging impacts including axotomy 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The spikes propagate to the ventral nerve cord ganglion [16][17][18] . The ultrastructure of this neuron was studied in detail in many works [19][20][21] . It proved itself a convenient model object for studying the response of neurons and glial cells to various damaging impacts including axotomy 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, since our original observation of the late 1960s, evidence for the exchange of molecules much larger than gap junction permeants between axons and sheath glial cells of crayfish and squid had surfaced [ 48 , 49 , 55 , 56 , 57 ], indicating that in some tissues, and exceptional circumstances, cell-cell communication could also be mediated by membrane pores. In the four decades that followed our 1981’s publication [ 53 ], only one study on crayfish stretch receptors confirmed the presence of membrane pores [ 58 ]. Therefore, for several decades the possibility that some cells might be able under special conditions to directly communicate via membrane pores was by and large ignored.…”
Section: Direct Cell-cell Communication Via Membrane Poresmentioning
confidence: 99%
“…Thus, even though diffusion is a limitation between gap junctions in communicated cells, several systems evolved to amplify these signals to other communicated cells. In the cell-to-cell pores, the possibilities are multiple, including the transfer of cytoplasmic soluble components, organelles, complexes of organelles, and even genetic material due to the large pore size observed by electron microscopy, 130–140 Å [ 53 , 58 ] ( Figure 4 , Figure 5 and Figure 6 ).…”
Section: Tnt or Cytonemes A New Concept For A Novel Long-rangementioning
confidence: 99%
“…Bcl-2 supports axon regeneration via CREB and ERK pathways, promoting Ca 2+ regulation by the endoplasmic reticulum [55].…”
Section: Calcium In Ultrastructural Response Of Neurons and Glia To A...mentioning
confidence: 99%
“…Ca 2+ and cAMP promote axon regeneration in C. elegans, engaging DLK-1 kinase [85]. Bcl-2 supports axon regrowth via the increase of intracellular Ca 2+ signaling and the activation of CREB and Erk proteins, promoting a regenerative response and neurogenesis; the expression of Bcl-2 decreases the intake and storage of Ca 2+ in ER and thus leads to a stronger intracellular Ca 2+ response, induced by Ca 2+ influx or axotomy in Bcl-2-expressing neurons, than in controls [55].…”
Section: Calcium Pathway In Death Survival and Regeneration Of Neuron...mentioning
confidence: 99%